Perceptions of an automotive load space in a virtual environment - Lawson, Glyn; Roper, Tessa; Herriotts, Paul; Malcolm, Louise; Salanitri, Davide (Inderscience, 2017)
A study was conducted to investigate the accuracy of perceptions of a car load space in a CAVE virtual environment. A total of 46 participants rated load space width, height, depth, usability and overall capacity after viewing either a virtual Range Rover Evoque in the CAVE or the real car. Participants were also asked to estimate how many 100mm3 blocks could fit in the load space in width, depth or height. The only significant difference was in usability, which was rated higher in the CAVE. There was no systematic over- or under-estimation of distances in the virtual environment. Equivalence was demonstrated for width and depth in the block estimation task. The results suggest that virtual environments can be used for car load space design, particularly for estimates of size, but further work is required to be confident that subjective ratings of virtual properties are equivalent to those of real vehicles.